The inhibitory effect of medication on the anaerobic co-digestion of food waste and brown water - Ng, Si Jia. (2013)
This report provides an insight to the inhibitory effect of two over-the-counter medications, i.e. paracetamol (acetaminophen) and aspirin, on the performance of the co-digestion of food waste and brown water. This research aims to study the feasibility of introducing a decentralized system to enhance the energy recovery of solid wastes that are being collected using different piping systems in a community. Surveys have found that some people have the tendency of disposing the expired/unconsumed medication into the toilets. The medication may have inhibitory effect towards microbial activities of anaerobic digestion downstream. The batch study was carried out using serum bottles for aspirin and Automatic Methane Potential Test System (AMPTS) for paracetamol. Biogas generation was selected as the main indicator to determine the inhibition effect that the medications have on anaerobic digestion. Other parameters such as pH, total chemical oxygen demand (TCOD), soluble chemical oxygen demand (SCOD), volatile fatty acid (VFA), total solids (TS), total suspended solids (TSS), volatile solids (VS) and volatile suspended solids (VSS) were used to cross reference the performance of the anaerobic digestion process. The inhibition level of both medications is likely to lie between 1mM and 10mM. It was observed that when paracetamol presented at concentration no more than 1mM, there was no significant impact on the biogas production. The cumulative net biogas production (sum of biogas produced daily) for the setups is in the following order: 1mM (592ml) < Control (596ml) <0.1mM (610ml). Aspirin enhanced the biogas production when the concentration was lower or equal to 1mM. The cumulative net biogas production for the setups is in the following order: 100mM (-22ml1) < 10mM (80ml) < Blank (312ml) < Control (583ml) < 0.1mM (608ml) < 1mM (619ml). The disposal of aspirin and paracetamol into the toilet is feasible at low concentration since the biogas production remains affected. However, medical practitioners could educate their patients on the proper medication disposal method as only two medications are investigated. Other organic compound may have severe effect to the environment. Proper and responsible disposal is the solution to pollution.